The impact of hospital volume on survival in patients with locally advanced colonic cancer. Issue 6 (23rd November 2022) - Rosander, Emma; Holm, Torbjörn; Sjövall, Annika; Hjern, Fredrik; Weibull, Caroline E; Nordenvall, Caroline
Abstract: Background: High hospital volume has been shown associated with improved survival in patients with several cancers. The aim of this nationwide cohort study was to investigate whether hospital volume affects survival in patients with locally advanced colonic cancer. Methods: All patients with non-metastatic locally advanced colonic cancer diagnosed between 2007 and 2017 in Sweden were included. Tertiles of annual hospital volume of locally advanced colonic cancer were analysed and 5-year overall and colonic cancer-specific survival were calculated with the Kaplan–Meier method. HRs comparing all-cause and colonic cancer-specific mortality rates were estimated using Cox models adjusted for potential confounders (age, sex, year of diagnosis, co-morbidity, elective/emergency resection, and university hospital) and mediators (preoperative multidisciplinary team assessment, neoadjuvant chemotherapy, radical resection, and surgical experience). Results: A total of 5241 patients were included with a mean follow-up of 2.7–2.8 years for low- and high-volume hospitals. The number of patients older than 79 years were 569 (32.3 per cent), 495 (29.9 per cent), and 482 (26.4 per cent) for low-, medium- and high-volume hospitals respectively. The 3-year overall survival was 68 per cent, 60 per cent and 58 per cent for high-, medium- and low-volume hospitals, respectively ( P < 0.001 from log rank test). High volume hospitals were associated with reduced all-cause and colon cancer-specific mortality after adjustments for potential confounders (HR 0.76, 95 per cent CI 0.62 to 0.93 and HR 0.73, 95 per cent CI 0.59 to 0.91, respectively). The effect remained after inclusion of potential mediators. Conclusions: High hospital volume is associated with reduced mortality in patients with locally advanced colonic cancer. Abstract : This was a national register-based study on the effect of hospital volume in patients with locally advanced colonic cancer that included 5241 patients. The study showed an association between high hospital volume and decreased mortality in patients with locally advanced colonic cancer.